Prognostic significance of grading (MIB-1 system) in patients with myxoid liposarcoma. Issue 8 (30th July 2003) - Tateishi, U; Hasegawa, T; Beppu, Y; Kawai, A; Moriyama, N
Abstract : Aims: To determine the relation between clinical outcome and tumour grade defined by a MIB-1 (Ki-67) score based grading system. Method: The clinical and pathological features of 50 patients with myxoid liposarcoma were evaluated, and MIB-1 immunostaining was performed to grade these patients' tumours. Univariate and multivariate analyses were conducted to evaluate survival. Clinical follow up details were available for all patients (median, 46.5 months; range, 9–408). Results: Univariate analysis revealed that the tumour site (p < 0.05), round cell component content (p < 0.01), necrosis (p < 0.01), mitosis (p < 0.01), MIB-1 labelling index (p < 0.001), and tumour grade (p < 0.001) had a significant impact on overall survival. Multivariate analysis showed that, of the variables evaluated, the tumour grade defined by a MIB-1 score based grading system was the most significant adverse prognostic factor. Conclusion: Tumour grade determined by the grading system using the MIB-1 score (MIB-1 system) is a very strong prognostic factor in patients with myxoid liposarcoma.